The portrait of challenges and strategies of village-owned enterprise in achieving SDGs: The perspective of sustainable development - Nugraheni, Tri Satya Rifah; Utami, Evy Rahman; Utami, Tiyas Puji (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study analyzed the challenges and strategies of the Tirta Mandiri Village-Owned Enterprise (VOE) in Ponggok Village, Klaten Regency, to reach the Sustainable Development Goals (SDGs). In addition, our study examines how VOE, as a social enterprise entity, can improve economic, social, and environmental sustainability at the village level.Design/Methodology/Approach: A qualitative approach with semi-structured interviews with administrators of VOE, the government of the village, beneficiaries, and VOE experts was used in this research, and it was used to explore the challenges and strategies of VOE.Research findings: The findings indicated that VOE had functioned as a social entrepreneurial entity. Tirta Mandiri VOE successfully empowered the community and generated wealth. Furthermore, VOE initiatives have accomplished the following SDGs: No Poverty (1), Quality Education (4), Gender Equality (5), Decent Work and Economic Growth (8), Industry, Innovation and Infrastructure (9), Climate Action (13), Life on Land (15), and Partnerships for the Goals (17). Nonetheless, numerous issues must be addressed, such as the evolving mindset of the community and constrained human resources. Furthermore, VOE encountered numerous competitors that operated analogous business units. These difficulties must be addressed through several techniques, including education, cultural literacy, and collaboration. VOE enhanced human resource capability, innovation, and delivery service. VOE served as an excellent mechanism for sustainable rural development.Practitioner/Policy implication: This study emphasized the importance of developing community empowerment and environmental sustainability programs by VOE and the need for greater support from local government to achieve SDGs effectively.Research limitation/Implication: This study had limitations, such as focusing on Tirta Mandiri VOE in Ponggok Village. In addition, a qualitative approach was used in this study.